Experimental study and numerical analysis on the vertical bracket of the plate buckle. (28th March 2019) - Zhang, Fengjian; Li, Guoyao; Shi, Zheng; Wei, Kelun; Zhang, Guangyao
In this paper, a new type of rotary plate buckle bracket is introduced, and the static loading test of the single span four-step vertical bracket system is carried out. Research and analysis the internal force transmission ways and failure modes of different types of tubes of the whole vertical bracket and plot of the load-displacement curve and load-strain curve. Using the ANSYS program, a numerical model is obtained which is consistent with the experimental results. The results of test and finite element analysis show that: the finite element calculation results are close to the ultimate bearing capacity of the new type of rotary plate buckle vertical bracket and under the ultimate load, the failure mode and the force of each tube are basically the same. The new type of rotary plate buckle vertical bracket is higher than that of traditional steel tubular scaffold with couplers and it has good economic benefit.